Tuning the Electromechanical Properties of PEDOT:PSS Films for Stretchable Transistors And Pressure Sensors. (18th April 2019) - Zhang, Shiming; Li, Yang; Tomasello, Gaia; Anthonisen, Madeleine; Li, Xinda; Mazzeo, Marco; Genco, Armando; Grutter, Peter; Cicoira, Fabio
Abstract: Poly(3, 4‐ethylenedioxythiophene) doped with polystyrene sulfonate (PEDOT:PSS) based organic electrochemical transistors (OECTs) have been widely applied in bioelectronics because of their low power consumption, biocompatibility, and ability to convert ionic biological signals into electronic signals with high sensitivity. Here, the processing of PEDOT:PSS thin films on soft substrates is reported for stretchable OECT applications. Enhanced stretchability of PEDOT:PSS films on elastic substrates is obtained by synergistically reducing the film thickness and decreasing the baking temperature. The resultant films, together with ultrathin Au electrodes, enable the assembling of fully stretchable OECTs using conventional fabrication techniques, without prestretching the substrates. The stretchable OECTs maintain similar electrical characteristics within 30% applied strain. It is also demonstrated that brittle PEDOT:PSS films, which are not suitable for making stretchable OECTs, can be used for transparent pressure sensors. Abstract : Thin films of the conducting polymer poly(3, 4‐ethylenedioxythiophene) doped with polystyrene sulfonate can be used for stretchable electrochemical transistors and pressure sensors.